Relationships among Tear Film Stability, Osmolarity, and Dryness Symptoms. Issue 9 (September 2015) - Yeh, Thao N.; Graham, Andrew D.; Lin, Meng C.
ABSTRACT Purpose To examine the relationships among tear osmolarity, tear film stability, and several measures of dry eye (DE) symptoms in a multivariable analysis. Methods A cross-sectional study was conducted with 137 subjects (68 non–contact lens [CL] wearers and 69 soft CL wearers) recruited from a university campus. Tear breakup time (TBUT) was measured noninvasively (NITBUT) and with fluorescein (FTBUT). Tear osmolarity was measured by an osmometer. Dry eye symptoms were assessed using the Dry Eye Flow Chart and several different questionnaires. Results Subjects ranged in age from 18 to 67 years, with a mean of 28 years. Subjects had a mean (SD) osmolarity of 293 (10) mOsm/L, NITBUT of 14.1 (10.9) seconds, and FTBUT of 14.8 (12.6) seconds. Shorter NITBUT and FTBUT were significantly associated with female sex (p = 0.001 and p = 0.027, respectively) and Asian ethnicity (p = 0.030 and p = 0.004, respectively). There were no clinically significant relationships between tear osmolarity and FTBUT, NITBUT, or DE symptoms. Higher Dry Eye Flow Chart score (i.e., worse symptoms) was associated with older age (p < 0.001), female sex (p = 0.014), CL wear (p < 0.001), shorter NITBUT (p < 0.001), and shorter FTBUT (p = 0.028). The sensitivities and specificities for using clinical measurements to diagnose moderate to severe DE were as follows: osmolarity, 0.67 and 0.46, respectively; NITBUT, 0.72 and 0.52, respectively; and FTBUT, 0.68 and 0.57, respectively. Conclusions In a population of asymptomatic, mild and moderate DE patients, increased tear osmolarity was not significantly associated with reported symptom severity and frequency. Tear osmolarity, NITBUT, and FTBUT exhibited similar sensitivities and specificities when used to diagnose moderate to severe DE.